2022
DOI: 10.1038/s41598-022-06363-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surface temperature variation of lakes in China using MODIS land surface temperature data

Abstract: China has a great wealth of lake resources over a great spatial extent and these lakes are highly sensitive to climate changes through their heat and water budgets. However, little is known about the changes in lake surface water temperature (LSWT) across China under the climate warming conditions over the past few decades. In this study, MODIS land surface temperature (LST) data were used to examine the spatial and temporal (diurnal, intra-annual, and inter-annual) variations in LSWT of China’s lakes during 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 43 publications
0
14
3
1
Order By: Relevance
“…Many potential drivers for warming LSWTs have been explored including the AT (Zhang G. et al, 2014;Piccolroaz et al, 2018), RF (Wan et al, 2018), WL (Zhang G. et al, 2014), water clarity (Rose et al, 2016), lake-specific morphology (water depth, water area, water storage) (Becker and Daw, 2005;Xie et al, 2022) and land use and land cover (Tan et al, 2020). Among these factors, the AT is widely considered a main driving factor for LSWT warming (Fink et al, 2014).…”
Section: Driving Force Of Lswt Warmingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many potential drivers for warming LSWTs have been explored including the AT (Zhang G. et al, 2014;Piccolroaz et al, 2018), RF (Wan et al, 2018), WL (Zhang G. et al, 2014), water clarity (Rose et al, 2016), lake-specific morphology (water depth, water area, water storage) (Becker and Daw, 2005;Xie et al, 2022) and land use and land cover (Tan et al, 2020). Among these factors, the AT is widely considered a main driving factor for LSWT warming (Fink et al, 2014).…”
Section: Driving Force Of Lswt Warmingmentioning
confidence: 99%
“…Many lakes and reservoirs worldwide have warmed over the past several decades, with varied warming rates (Schneider and Hook, 2010;O'Reilly Catherine et al, 2015;Xie et al, 2022). From 1986 to 2021, the LSWTs of Lake Qiandaohu displayed a significant increasing trend, with a warming rate of 0.07 °C/year.…”
Section: Implications For the Lake Thermal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Yamak and Comert [27] used Landsat images for the extraction of the Land Surface Temperature (LST) map, and low LST values were observed in vegetated areas, forest areas, and wetlands. In the study of Xie et al [28], MODIS LST data were used to examine the spatial and temporal variations in lake surface water temperature (LSWT) of China's lakes between 2001 and 2016. Their findings indicated that the 169 large lakes included in the study had an overall increasing trend in LSWT, with an average rate of 0.26 • C/decade.…”
Section: Introductionmentioning
confidence: 99%
“…The largest LST variability between lakes however for summer was twice that of winter (16°C). This is expected as temperatures on lakes during this season are influenced by several factors including lake size, elevation, depth, latitude, longitude and volume(O'Reilly et al, 2015;Xie et al, 2022) in addition to air temperature. Seasonal LST spatial distribution provides an insight into the climate patterns of the NSR region.…”
mentioning
confidence: 97%